Spatial feeding preferences of ornithophilic mosquitoes, blackflies and biting midges - Cerný, O; Votýpka, J; Svobodová, M (Medical and veterinary entomology, 2011)
The section of habitat used by particular bloodsucking insects when seeking bloodmeals may influence the spectrum of hosts to which they have access and consequently the diseases they transmit. The vertical distribution of ornithophilic bloodsucking Diptera (Culicidae, Simuliidae and Ceratopogonidae) was studied using bird-baited traps set at both ground and tree canopy levels. In total, 1240 mosquito females of eight species, 1201 biting midge females of 11 species, and 218 blackfly females of two species were captured during 2003-2005. Culex pipiens (L.) (Diptera: Culicidae) was found to prefer ground-level habitats, whereas Anopheles plumbeus (Stephens) (Diptera: Culicidae), biting midges [Culicoides spp. (Diptera: Ceratopogonidae)] and Eusimulium angustipes (Edwards) (Diptera: Simuliidae) preferred the canopy. The results of this study with regard to Cx. pipiens behaviour differ from those of most previous studies and may indicate different spatial feeding preferences in geographically separate populations. The occurrence of E. angustipes in the canopy is concordant with its role in the transmission of avian trypanosomes. These findings may be important for surveillance programmes focusing on ornithophilic Diptera which transmit various pathogenic agents.
Keywords: Simuliidae; Behavior, Animal; Trypanosomiasis; stravovací zvyklosti; Ecosystem; trypanozomiáza; Česká republika; hmyz - vektory; nemoci ptáků; Czech Republic; ptáci; Birds; Animals; ženské pohlaví; zvířata; Culicidae; Ceratopogonidae; Bird Diseases; chování zvířat; ekosystém; Insect Vectors; Female; Trypanosoma; Feeding Behavior